Upper Structure Design of Liquid Berth 1 with Precast Concrete in Magtymguly Gas Recycling Development Project at Caspian Sea - Pramayuda, Kemal
Liquid Natural Gas is an alternative energy that produced cleaner combustion. To fulfill the needs of LNG logistics, infrastructure like liquid berth is needed. One of them is Liquid Berth 1, that is located on Magtymguly Gas Recycling Development Project at the Caspian Sea, that has been designed before. Preliminary designs of the berth consist of dimensions, horizontal and vertical load that will be reviewed by using British Standard. The dimensions and loads that have been reviewed, must be optimal and thus it will be modelled using SAP2000. The results of the model are unity check ratio, displacement and internal forces for beam, slab, and pile cap. The value of internal forces will be used to design the reinforcement bar. Liquid berth 1 will be designed again by using precast concrete. There are many advantages that can be obtain by using precast concrete. Design using precast concrete needed 3 analyses that must be conducted. The analyses are lifting condition, installation condition, and support condition. Lifting analysis will check the strength of the reinforcement bar and the requirement of lifting anchor. Installation condition will check the strength of the element when maintaining self- weight and receiving another element. Support condition will check the possibility of shear failure at the supporting area.